Mortality reduction in pediatric patients with severe fatal human adenoviral pneumonia treated with high titer neutralizing antibodies (NAbs) plasma: a retrospective cohort study - Hongyan Peng; Feiyan Chen; Yunlong Zuo; Bolun Huang; Yiyu Yang; Run Dang (BMC, 2022)
Abstract Background Severe fatal human adenoviral (HAdV) pneumonia is associated with significant mortality and no effective drug is available for clinical therapy. We evaluated the association and safety of high titer neutralizing antibodies (NAbs) plasma in pediatric patients with severe fatal HAdV pneumonia. Methods A retrospective cohort study was performed between January 2016 to June 2021 in pediatric intensive care unit. Pediatric patients with severe fatal HAdV pneumonia were included and divided into plasma group (conventional treatment plus high titer NAbs plasma treatment) and control group (conventional treatment alone). The primary outcome was mortality in hospital. Secondary outcomes were the duration of fever after adenovirus genotype determined, duration of invasive mechanical ventilation, length of hospital stay. T-test, Mann-Whitney U-test, chi-square test, univariable and multivariable logistic regression analysis, Kaplan-Meier method and log-rank test were adopted to compare differences between two groups. Results A total of 59 pediatric patients with severe fatal HAdV pneumonia were enrolled. They were divided into plasma group (n = 33) and control group (n = 26). The mortality in hospital was 28.8% (17/ 59). Significantly fewer patients progressed to death in plasma group than control group (18.2% vs 42.3%, p = 0.042). Sequential organ failure assessment (SOFA) score, oxygen index (OI) and high titer NAbs plasma treatment were included in multivariable logistic regression analysis for mortality risk factors. Consequentially, SOFA score (Hazard Ratio [HR] 7.686, 95% Confidence Interval [CI] 1.735-34.054, p = 0.007) and without high titer NAbs plasma treatment (HR 4.298, 95%CI 1.030-17.934, p = 0.045) were significantly associated with mortality. In addition, high titer NAbs plasma treatment were associated with faster temperature recovering in survivors (p = 0.031). No serious adverse effects occurred. Conclusions Administration of high titer NAbs plasma were associated with a lower hazard for mortality in pediatric patients with severe fatal HAdV pneumonia. For survivors, high titer NAbs plasma treatment shorten the duration of fever.